2007
DOI: 10.4319/lo.2007.52.6.2358
|View full text |Cite
|
Sign up to set email alerts
|

Change in filter‐screen morphology and depth selection: Uncoupled responses of Daphnia to the presence of filamentous cyanobacteria

Abstract: In many eutrophic lakes, ability to cope with filamentous cyanobacteria is crucial to Daphnia fitness, as the filaments can reduce food intake by interference with food-particle retention. Two basic mechanisms were proposed to explain food collection by Daphnia: mechanical sieving, in which filtering appendages act as sieves, and direct interception, in which appendages act as paddles and water does not pass through. As was recently suggested, both mechanisms may be active, and their relative importance is det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…We speculate that the thickening and shortening of Aphanizomenon filaments help individuals to avoid mechanical destruction. Bednarska and Dawidowicz (2007) observed in Daphnia a reduction in intersetal and intersetular distances in the filtering apparatus to reduce the interference from filamentous cyanobacteria. The shortening and thickening of a filament may make it easier to pass through the filtering chamber without being destroyed or eaten.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the thickening and shortening of Aphanizomenon filaments help individuals to avoid mechanical destruction. Bednarska and Dawidowicz (2007) observed in Daphnia a reduction in intersetal and intersetular distances in the filtering apparatus to reduce the interference from filamentous cyanobacteria. The shortening and thickening of a filament may make it easier to pass through the filtering chamber without being destroyed or eaten.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in mesh sizes allows Daphnia to intercept small bacteria (Brendelberger 1991), which may compensate for unfavorable nutritional conditions. The presence of filamentous cyanobacteria caused decreased intersetal and intersetular distances in the filtering apparatus, and elongation of filtering setae in Daphnia (Machá-ček 1998;Bednarska and Dawidowicz 2007). The latter authors suggested that such morphological changes reduce the interferential effect of cyanobacterial filaments on the filtration process.…”
Section: Introductionmentioning
confidence: 99%
“…Although modifications of the filtration apparatus of Daphnia have been broadly studied on numerous Daphnia species (Macháček 1998;Repka et al 1999a, b;Ghadouani and Pinel-Alloul 2002;Bednarska and Dawidowicz 2007), little has been known about the changes in the thickness of setae induced by filamentous cyanobacteria. Because the distance between setae decreases in response to the presence of cyanobacteria (Bednarska and Dawidowicz 2007) and the number of setae on filtering appendages is constant in adult animals (Pop 1991;Lampert and Brendelberger 1996), it is reasonable to expect the setae to become thicker in such conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to measurement, the animals were preserved in 4% sugar formaldehyde and the endopodites were dissected from the third pair of thoracic legs of each individual (two endopodites per Daphnia) and transferred in a drop of glycerol onto a microscope slide (Bednarska and Dawidowicz 2007). The filter screens were then photographed and inter-setular distances were measured at 10 locations in the middle of the setae using MultiScan image analysis software.…”
Section: Efficiency Of Exploitation Of Bacterial Foodmentioning
confidence: 99%